Posisi Subjek Tokoh Skeeter dalam Filem The Help (2011) Karya Tate Taylor: Kajian Subjektivasi Slavoj Žižek - Nor Holis; Aprinus Salam (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
Slavoj Žižek introduces definition of subject through the concept of The Real. He decribes it use the Lacan’s psychoanalys triagle. The process of reaching The Real causes the subject to do something that can be out of the symbolic. Therefore, the position of subject could be decided at this stage. This kind of subject is seen in The Help (2011) film. It is represented by Skeeter. She tries to out from the symbolic order to get the real. In her process to reach the real, she is unable to release herself from the symbolic completely because of her educational background, her thought, and her conscience. Therefore, Skeeter could not be defined as the radical subject based on the process. Still, her effort in order to out from the symbolic is never succeeded. It is because she always does everything with full consideration. In fact, she only moves to the new symbolic order.